Effectiveness of Mangrove Leaf Extract (Rhizophora apiculata) in Preventing Vibrio alginolyticus Infection in White Snapper (Lates calcarifer) - Afrina Afrina; Agus Putra; Suri Purnama Febri; Suraiya Nazlia (Jurnal Media Akuakultur Indonesia, 2025)
White snapper (Lates calcarifer) is a marine fish that has important economic value and contains high nutritional value as a consumption fish. In the white snapper cultivation system, the emergence of disease outbreaks is one of the main threats. One of the diseases that often occurs in white snapper cultivation is bacterial disease. The type of bacteria that causes serious disease and threatens the economy and sustainability of white snapper production is Vibrio alginolyticus.This study aims to analyze the effectiveness of soaking mangrove leaf extract (Rhizophora apiculata) in white snapper to prevent Vibrio alginolyticus and to determine the appropriate dose of mangrove leaf oil extract to prevent Vibrio alginolyticus bacterial disease.The research method used is a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatments were: P1 = 0 ml mangrove extract/L, P2 = 0.5 ml mangrove extract/L, P3 = 1.5 ml mangrove extract/L and P4 = 2.5 ml mangrove extract/L Results: The best healing time was found in P4 with a duration of 23 hours and the best survival was also found in P4 with a percentage of 96.67%, while the lowest survival was found in P1 at 56.67%. The range of water parameters during the study were temperature in the range of 28oC-29oC, pH 8, DO 4-5 mg/L water, salinity 31 ppt, ammonia 0.4, nitrate <0.01 and nitrite <0.1. The conclusion of this study is that soaking in standard oil leaf extract is effective in preventing Vibrio alginolyticus bacteria in white snapper.